Beyond disciplinary consumption in program planning courses: Dilemmas in teaching with and about power. - Arthur L. Wilson; Ronald M. Cervero (Adult Education Research Conference, 1997)
Power matters in teaching program planning because such courses are not just mere sites of instruction but are also mechanisms for constructing power relations. In the paper we raise questions about dilemmas and responsibilities faced by faculty and students once issues around power are made transparent in the curriculum itself.